The cytogenetics of childhood acute leukemia - Raimondi, Susana C. (Henry Stewart Talks, 2016)
Application of new diagnostic techniques in clinical medicine, mainly in molecular cytogenetics of neoplasia, Relevant chromosomal abnormalities that impact the diagnosis and prognosis of patients with acute lymphoblastic leukemia and acute myeloblastic leukemia